Studi Literatur Pengaruh Massa Adsorben dalam Proses Pemurnian Minyak Jelantah Menggunakan Adsorben Arang Aktif dari Ampas Tebu - Irmawati Syahrir; Abdul Halim; Firman Firman; Ahmad Amrullah (MEDIA PERSPEKTIF : Journal of Technology, 2020)
A repeatedly used cooking oil is also called as used cooking oil. Used cooking oil from 17 entrepreneurs in Palaran Sub-District is 161,5 liters/day or 50,65 tons/year. Used cooking oil can result in pollution to the environment due to the increasing number of acids and the number of peroxide. The research objectives of this literature study is to find out the effects of the mass adsorbent in the refining process of cooking oil with the activated charcoal adsorbent from sugar cane on the number of acids and the number of peroxide. A lot of sugar cane has a content of cellulose 45%, lignin 18%, Pentosan 32% and others 5%, so it can be used as a material of active charcoal which can be applied as adsorbent for the purification of used cooking oil. The process of refining the oil using adsorption method by varying the mass of active charcoal adsorbent. The collection of secondary data on the research of this literature was sourced from Triyanto (2013), Irmawati and Syahrir (2018) and Bariah (2020) who have examined the mass influence of active charcoal adsorbent on the number of acids and numbers of peroxide. Based on the results of analysis and interpretation of the third data of the journal used obtained information that the mass recommendation adsorbent on mass 6 grams